Practicality of Project Model Learning Tools Assisted by Augmented Reality to Improve Scientific Literacy and Creative Thinking Skills - Harjono, Ahmad; Hadiprayitno, Gito; Naf'atuzzahrah, Naf'atuzzahrah (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
This research aims to determine the practicality of project model learning tools assisted by augmented reality to improve students' scientific literacy and creative thinking skills. This development research procedure refers to the stages in the 4D model which consists of four main stages, namely definition, design, development and dissemination. Practicality testing is carried out at the development stage after the definition and design stages. The instruments used for the practicality test consisted of observation sheets on learning implementation, teacher and student response questionnaires. The observers involved in filling in the learning implementation observation sheet and response questionnaire were 1 science teacher and 20 class VIII students islamic junior high school (MTs) in West Lombok, NTB. The results of the observation analysis of learning implementation at the first, second and third meetings were 91%, 97% and 99% respectively in the very practical category. The results of the analysis of teacher and student responses have a percentage of 97% and 93% in the very practical category. These results show that the tools developed are practical to apply in science learning.